Expression of the ISPpu9 transposase of Pseudomonas putida KT2440 is regulated by two small RNAs and the secondary structure of the mRNA 5′-untranslated region. Issue 16 (11th August 2021) - Gómez-García, Guillermo; Ruiz-Enamorado, Angel; Yuste, Luis; Rojo, Fernando; Moreno, Renata
Abstract: Insertion sequences (ISs) are mobile genetic elements that only carry the information required for their own transposition. Pseudomonas putida KT2440, a model bacterium, has seven copies of an IS called ISPpu9 inserted into repetitive extragenic palindromic sequences. This work shows that the gene for ISPpu9 transposase, tnp, is regulated by two small RNAs (sRNAs) named Asr9 and Ssr9, which are encoded upstream and downstream of tnp, respectively. The tnp mRNA has a long 5′-untranslated region (5′-UTR) that can fold into a secondary structure that likely includes the ribosome-binding site (RBS). Mutations weakening this structure increased tnp mRNA translation. Asr9, an antisense sRNA complementary to the 5′-UTR, was shown to be very stable. Eliminating Asr9 considerably reduced tnp mRNA translation, suggesting that it helps to unfold this secondary structure, exposing the RBS. Ectopic overproduction of Asr9 increased the transposition frequency of a new ISPpu9 entering the cell by conjugation, suggesting improved tnp expression. Ssr9 has significant complementarity to Asr9 and annealed to it in vitro forming an RNA duplex; this would sequester it and possibly facilitate its degradation. Thus, the antisense Asr9 sRNA likely facilitates tnp expression, improving transposition, while Ssr9 might counteract Asr9, keeping tnp expression low.